Polymer Electrolyte a Novel Material for Electrochemical Devices: A Review. Issue 1 (1st August 2022) - Singh, Palvinder; Sachdeva, Amit; Bhargava, Cherry
Abstract: Polymer Electrolyte is novel material as renewal energy sources are widely used in the industries. Electrolyte is the main parts of storing/conversion devices. In this review article polymer electrolyte novel material are discussed. In this report various polymer advantage, application, availability, categories of polymer, various approaches, and sample preparation techniques are also described. Polymer electrolyte also used in batteries, fuel cells, supercapacitors, Dye-sensitizes solar cell and energy storing/conversion devices. It is observed that polymer electrolyte is better awareness to the researchers and readers.